"An Ontological Crisis": Sartre's Gaze and Being-for-Others in Zoë Wicomb's Playing in the Light. Issue 1 (2nd January 2018) - Ateh Laue, Kharys
Summary: This article on Zoë Wicomb's Playing in the Light uses as its point of departure her remark that "there must be an ontological crisis [for play-whites] that nobody can talk about, because officially they don't exist". Jean-Paul Sartre's notion of Being-for-Others, as well as W.E.B. du Bois's and Franz Fanon's work on black double consciousness, frame my contention that, for the two central characters Helen and Marion, the gaze of other people is at the root of their "ontological crisis" or destabilisation of being. In the article I develop my own interpretation of Sartre's theory of the gaze and distinguish between two potential forms of the look, which I call the prejudiced-look and the critical-look. I argue that the experience of for-Others, depending on the nature of the Sartrean look, has the potential to trigger either an inescapable alienation from self (in the case of Helen) or a development of self (in the case of Marion). So, for instance, Helen's exposure to the prejudiced white gaze results in her physical and mental deterioration, whereas Marion's experience of the critical gaze enables constructive internal changes. Ultimately, my article aims to shed new light on the complex dynamics of the gaze, intersubjectivity, and ontological anxiety in the racially charged space of South Africa.